Laryngeal cancer risks in workers exposed to lung carcinogens: exposure-effect analyses using a quantitative job exposure matrix - Hall, Amy L.; Ramroth, Heribert; Ahrens, Wolfgang (Epidemiology, 2020)
Introduction: - Various established occupational lung carcinogens are also suspected risk factors for laryngeal cancer. However, individual studies are often inadequate in size to investigate this relatively rare outcome. Other limitations include imprecise exposure assessment and inadequate adjustment for confounders. - Methods: - This study applied a quantitative job exposure matrix (SYN-JEM) for four established occupational lung carcinogens to five case-control studies within the International Head and Neck Cancer Epidemiology Consortium. We used occupational histories for 2256 laryngeal cancer cases and 7857 controls recruited from 1989 to 2007. We assigned quantitative exposure levels for asbestos, respirable crystalline silica, chromium-VI, and chromium-VI and nickel combined (to address highly correlated exposures) via SYN-JEM. We assessed effects of occupational exposure on cancer risk for males (asbestos, respirable crystalline silica, chromium-VI, and chromium-VI and nickel combined) and females (asbestos and respirable crystalline silica), adjusting for age, study, tobacco smoking, alcohol consumption, and asbestos exposure where relevant. - Results: - Among females, odds ratios (ORs) were increased for ever versus never exposed. Among males, P values for linear trend were <0.05 for estimated cumulative exposure (all agents) and <0.05 for exposure duration (respirable crystalline silica, chromium-VI, and chromium-VI and nickel combined); strongest associations were for asbestos at >90th percentile cumulative exposure (OR = 1.3, 95% confidence interval [CI] = 1.0, 1.6), respirable crystalline silica at 30+ years duration (OR = 1.4, 95% CI = 1.2, 1.7) and 75th-90th percentile cumulative exposure (OR = 1.4, 95% CI = 1.1, 1.8), chromium-VI at >75th percentile cumulative exposure (OR = 1.9, 95% CI = 1.2, 3.0), and chromium-VI and nickel combined at 20-29 years duration (OR = 1.5, 95% CI = 1.1, 2.2). - Conclusions: - These findings support hypotheses of causal links between four lung carcinogens (asbestos, respirable crystalline silica, chromium-VI, and nickel) and laryngeal cancer.
Gesehen am 20.04.2020